Reactivation of Paleozoic structures during Cenozoic deformation in the Cordón del Plata and Southern Precordillera ranges (Mendoza, Argentina) - Giambiagi, Laura Beatriz (2014)
The tectonic style of the eastern morphostructural units of the Central Andes between 32°20´ and 33°20´S is strongly influenced by pre-Andean structures, especially those developed during the late Carboniferous-Early Permian San Rafael orogeny of the Gondwanan orogenic cycle. Moreover, in the study area pre-Carboniferous rocks were deformed in Late Devonian-early Carboniferous times by the Chanic orogeny. In this paper we argue that the Cordón del Plata and the Southern Precordillera ranges, first order features of the eastern ranges of the Andes, have been shaped in large part by the Permian event. Our data suggest that the double verging character of the Andean Precordillera fold- thrust belt is mainly the result of the reactivation of Gondwanan structures which conform a fold-thrust belt with distinct characteristics north and south of 33°S. The northern sector of this belt corresponds to a bivergent system, while the southern sector had a widespread east vergence. The vergence of the Chanic structures is more difficult to determine, but we infer a westward vergence in the Frontal Cordillera and western sector of Precordillera, and an eastern vergence in the eastern sector of the Precordillera. The sharp disappearance of the Precordillera morphostructural unit south of 33°S is inferred here to be related to the distribution of inherited Permian structures.